Exploring the feasibility of using different cellular telephone based messaging platforms as demand creation channels for voluntary medical male circumcision in Gauteng, South Africa - Coats, Gareth Michael (My University, 2015)
Three randomised control trials in Kenya, Uganda and South Africa have shown that Voluntary Medical Male Circumcision (VMMC) reduces the risk of heterosexual HIV transmission to men by up to 60%. This has resulted in a WHO and UNAIDS recommendation to promote VMMC as part of comprehensive HIV prevention programming. In order for South Africa to achieve its 80% national coverage target of VMMC, significant investment needs to be made in demand creation programming. The Centre for HIV/AIDS Prevention Studies (CHAPS) provides free VMMCs through 28 community based clinics and hospitals in Gauteng, North West and Limpopo Provinces. In 2013, CHAPS demand creation activities have resulted in some increases in demand but CHAPS have committed to exploring additional demand creation opportunities. In terms of reach, mobile telephones are highly prevalent in South Africa, with more than 90% of South African households surveyed in 2011 reporting to have at least one cellular telephone in the home. The ongoing advancement of mobile phones to allow data transfer and internet access also means that more ‘Technology-Poor’ or ‘ICT Have-nots’ will be able to access the ever increasing knowledge content of the internet, participate in digital social-domains and be reached in shorter times and at lower costs.
A research report submitted to the School of Public Health, University of WItwatersrand in partial completion of the requirements of the degree Master of Public Health : Social and Behaviour change communication
Keywords: Circumcision, Male; Information Systems